(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Ornithological research was carried out in 2019-2020. 48 species belonging to the order of Passeriformes have been identified on the territory of the Sarkent State Natural Park. Among the 48 species of birds living in various natural ecosystems, only 3 species (rock swallow (Riparia rupestris), black crow (Corvus corone) and common lentil (Carpodacus erythrinus) are most common. And the remaining 17 species can be attributed to low numbers, 16 species are rare and 6 too rare species.